Activated leucocyte cell adhesion molecule (ALCAM/CD166) regulates T cell responses in a murine model of food allergy. (20th February 2018) - Kim, Y. S.; Kim, M. N.; Lee, K. E.; Hong, J. Y.; Oh, M. S.; Kim, S. Y.; Kim, K. W.; Sohn, M. H.
Summary: Food allergy is a major public health problem. Studies have shown that long‐term interactions between activated leucocyte cell adhesion molecule (ALCAM/CD166) on the surface of antigen‐presenting cells, and CD6, a co‐stimulatory molecule, influence immune responses. However, there are currently no studies on the functions of ALCAM in food allergy. Therefore, we aimed to identify the functions of ALCAM in ovalbumin (OVA)‐induced food allergy using ALCAM‐deficient mice. Wild‐type (WT) and ALCAM‐deficient (ALCAM –/– ) mice were sensitized intraperitoneally and with orally fed OVA. The mice were killed, and parameters related to food allergy and T helper type 2 (Th2) immune responses were analysed. ALCAM serum levels increased and mRNA expression decreased in OVA‐challenged WT mice. Serum immunoglobulin (Ig)E levels, Th2 cytokine mRNA and histological injuries were higher in OVA‐challenged WT mice than in control mice, and these were attenuated in ALCAM –/– mice. T cell proliferation of total cells, CD3 + CD4 + T cells and activated T cells in immune tissues were diminished in OVA‐challenged ALCAM –/– mice. Proliferation of co‐cultured T cells and dendritic cells (DCs) was decreased by the anti‐CD6 antibody. In addition, WT mice sensitized by adoptive transfer of OVA‐pulsed ALCAM –/– BM‐derived DCs showed reduced immune responses. Lastly, serum ALCAM levels were higher in children with food allergy than in control subjects. In this study, serum levels of ALCAM were elevated in food allergy‐induced WT mice and children with food allergy. Moreover, immune responses and T cell activation were attenuated in OVA‐challenged ALCAM –/– mice. These results indicate that ALCAM regulates food allergy by affecting T cell activation. Abstract : The number of CD3+CD4+ T cells was enhanced throughout the immune tissues, especially in the small intestine, of OVA‐challenged WT mice when compared to the numbers of T cells in control WT mice. However, the number of CD3+CD4+ T cells was lower in OVA‐challenged ALCAM‐/‐ mice than in OVA‐challenged WT mice. We also found that the number of activated cells (CD4+CD44highCD62Llow) decreased in OVA‐challenged ALCAM‐/‐ mice than in OVA‐challenged WT mice.